Faktor Transfer 137cs Dari Tanah Bengkayang Ke Tanaman Jagung (Zea mays) - Nirwani, Leli; Wahyudi, Wahyudi; Suharyono, Gatot; Maulidia, Maulidia (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Nirwani, L., Wahyudi, W., Suharyono, G., & Maulidia, M. (2023). Transfer factor 137cs from bengkayang soil to corn plants (Zea mays). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang, 21 Oktober 2023. (pp. 581-590). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This research aimed to obtain the transfer factor value of 137Cs from Bengkayang soil to corn plants. A pot experiment using a completely randomized design tested two treatments, namely soil that had been contaminated with 137Cs and without 137Cs (control). After harvest, the dry weight of the plants was measured and measurements were made using a Gamma Spectrometer of the concentration of 137Cs in dry plants and dry soil to obtain values. the transfer factors. The results of preliminary soil analysis obtained a soil pH of 6.4, this value is a good pH value for the growth of corn plants, namely 5.5 – 7. The organic matter content of the soil is classified as low to medium. The soil texture used in the experiment was sandy clay loam which consisted of 76% sand, 9% dust and 15% clay, a soil texture that was good enough for the growth of corn plants. The transfer factor value of 137Cs from Bengkayang soil to corn plants is between 0.6396 - 4.6336 with an average value of 2.0814, where the value obtained is higher when compared to data released by the IAEA (2010), namely the transfer factor from soil to corn plants is 0.0030 – 0.4900.